The Impact of the Covid-19 Pandemic on Reserve Adequacy: Evidence From Middle Income Countries - Etta-Nkwelle, Maru; Augustine, Carlton; Hunte, Cyril Kenrick (Journal of Applied Business and Economics, 2021)
In order to examine the impact of the COVID-19 pandemic on reserve adequacy levels in 70 middle income EMC’s we employ the IMF’S risk weighted metric, along with three other standard measures. Our research suggests that over 50% of these countries were ill-prepared to handle the financial risks posed by COVID- 19 beyond 2020. We find that the demand for international reserves during the study period emphasized financial stability, rather than trade related vulnerabilities. We observed that reserve demand is influenced by the need to meet a more broad-based adequacy level, with less emphasis on individual sectorial vulnerabilities. Additionally, the financial stability variables, such as the dummy variable for the fixed exchange rate, broad money/reserves, and short-term debt/ reserves, carry a greater proportion of the weights than the trade related variables, namely, (export + import)/GDP, export/GDP, and import/GDP. This finding lends support to the notion that the motivations for holding reserves by EMCs may be shifting away from trade related vulnerabilities and moving towards mitigating susceptibilities in the financial sector.